Production and Input-use Efficiency in the Sawmilling Industry of Peninsular Malaysia - Othman, Mohd Shahwahid (1985)
Production functions for the sawmilling industry in three states of Peninsular Malaysia are estimated. Sawntimber output is regressed with gross capital and labour as independent variables. The returns to scale underlying the sawmilling industry are estimated. The findings of this study do provide useful indications on efficiency of input utilisation, subject to potential sources of bias noted in the paper.